How Available Facilities Affect a Teachers Performance - AlKahtani, Aishah Abdulaziz (Social Science Learning Education Journal, 2016)
Teacher well-being is upheld as an important factor in terms of improving the quality of teaching and school effectiveness (Leithwood, et al., 2006). The questionnaire survey, conducted in April/May 2009, was undertaken in two major cities in Saudi Arabia with an opportunistic sample of teachers (n = 445) drawn from 22 schools, both boysâ and girlsâ schools. The questionnaire consisted of fixed-response items except a final open-ended question. The questionnaire sought to discover how teachers reacted to their working conditions. The study concludes by urging the Saudi Ministry of Education to improve the quality of facilities in its classrooms and to examine its in-service training provision. These changes would help teachers develop their teaching skills and provide a better quality of education for their students. It is important that teachersâ views and opinions are sought when bringing about improvements. The researcher also considers what she has learned about research work from conducting the study. In conclusion, she calls on the Ministry of Education when developing its provision, to take more account of the views of teachers. They have firsthand experience of working in Saudi classrooms; as such, they represent a valuable resource, which should be supported and encouraged.